Photosynthetic activity and metabolic profiling of bread wheat cultivars contrasting in drought tolerance - Ghaffar, Abdul; Hussain, Nadeem; Ajaj, Rahaf; Shahin, Suzan Marwan; Bano, Hussan; Javed, Muhammad; Khalid, Ayesha; Yasmin, Memoona; Shah, Kausar Hussain; Zaheer, Muhammad; Iqbal, Muhammad; Zafar, Zafar Ullah; et al. (Frontiers in Plant Science, 2023)
Rapid increase in population growth under changing climatic conditions causes drought stress threatening world food security. Identification of physiological and biochemical traits acting as yield limiting factors in diverse germplasm is pre-requisite for genetic improvement under water deficit conditions. The study was conducted to screen 40 local wheat cultivars against drought stress at different growth stages. Barani-83, Blue Silver, Pak-81 and Pasban-90 exhibited less decrease in biomass, N, P, K and quantum yield of PSII under PEG-induced drought stress at seedling stage and can be considered as tolerant while more reduction in these parameters make FSD-08, Lasani-08, Punjab-96 and Sahar-06 as drought sensitive cultivars. FSD-08 and Lasani-08 could not maintain growth and yield due to protoplasmic dehydration, decreased turgidity, cell enlargement and cell division due to drought treatment at adult growth stage. Stability of leaf chlorophyll content reflects photosynthetic efficiency of tolerant cultivars while increase in proline, free amino acids and soluble sugars was associated with maintaining leaf water status by osmotic adjustment. Raw OJIP chlorophyll fluorescence curves revealed decrease in fluorescence at O, J, I and P steps in sensitive genotypes FSD-08 and Lasani-08 showing greater damage to photosynthetic machinery and greater decrease in JIP-test parameters, performance index (PIABS), maximum quantum yield (Fv/Fm) associated with increase in Vj, absorption (ABS/RC) and dissipation per reaction center (DIo/RC) while decrease in electron transport per reaction center (ETo/RC). Selected tolerant cultivars could be explored in various breeding programs to produce new wheat genotypes with adaptive traits to withstand water stress.